Think-Pair-Share as a Strategic Solution to Strengthen Self-Confidence in Arabic Speaking Skills - Zahro, Shella Laili; Dimyati, Muh. (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This quantitative study aims to analyze the Think-Pair-Share (TPS) learning model as a strategic solution to strengthen students' confidence in speaking Arabic. The low self-confidence of students in speaking Arabic at MA Alamiriyyah in Banyuwangi, East Java, provides the background for this research. The population consists of all tenth-grade students, and a sample of 50 students was selected using purposive sampling based on similarities in initial abilities and demographic characteristics. The sample was divided into an experimental group (n = 25) and a control group (n = 25). A quasi-experimental design with an unequal control group was used. Data were collected through pretest and posttest speaking performance tests that have been validated for validity and reliability, and analyzed using descriptive statistics and the Mann-Whitney U test. The results show that the TPS model significantly increases confidence, as evidenced by the difference in posttest means between the experimental group (M = 83.20) and the control group (M = 73.40) at p < 0.001, with a large effect size (r = 0.50) and a moderate N-Gain (0.65). Thus, the TPS model can serve as a strategic solution through a collaborative approach that not only strengthens linguistic competence but also the affective aspects in Arabic language learning at madrasahs. This study recommends implementing TPS to address psychological issues in second-language acquisition.